Energy-Efficiency Optimization-Based User Selection and Power Allocation for Uplink NOMA-Enabled IoT Networks - Wu, Yali; Liu, Shuangxiao; Lin, Xiaoran; Sun, Lei (2023 IEEE 12th International Conference on Educational and Information Technology (ICEIT), 2023)
Non-orthogonal multiple access (NOMA) is a key spectrally-efficient technology to support a mass of data transmission for Internet of Things (IoT) networks. In this paper, we propose a novel user selection and power allocation scheme to optimize the overall energy efficiency for uplink NOMA-enabled IoT networks. First, the energy efficiency maximization problem is formulated with a per-user outage probability and transmit power constraints. Then we solve the optimization problem by developing an iterative algorithm. Furthermore, a user selection scheme on account of the path loss and the difference of received power among multiplex users is considered to share the same spectrum resource for data transmission. The analytic model is validated by simulation results. Simulation results show that the proposed system can efficiently improve energy efficiency compared with other algorithms.